If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9-4x=3+x2
We move all terms to the left:
9-4x-(3+x2)=0
We add all the numbers together, and all the variables
-(+x^2+3)-4x+9=0
We get rid of parentheses
-x^2-4x-3+9=0
We add all the numbers together, and all the variables
-1x^2-4x+6=0
a = -1; b = -4; c = +6;
Δ = b2-4ac
Δ = -42-4·(-1)·6
Δ = 40
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{40}=\sqrt{4*10}=\sqrt{4}*\sqrt{10}=2\sqrt{10}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-2\sqrt{10}}{2*-1}=\frac{4-2\sqrt{10}}{-2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+2\sqrt{10}}{2*-1}=\frac{4+2\sqrt{10}}{-2} $
| -5(-5x+2)-4x=5(x-3)-7 | | 15.6=7.8x | | (4x+13)+(6x+2)+(180-(14x-13))=180 | | 5+x/6=-6 | | 27=9*3+8y | | -q+1=2q+10 | | 3(b+1)+1=4b | | -(p+3/5)=-4 | | x=(2^23)*(2^23) | | 8a+15=-1 | | 10+2r-8=10+4r | | d−35=50 | | 7(w-84)=63 | | 60=8x+44 | | 68=k+15 | | (-4x+43)=(-6x-13) | | -5.5x=-22 | | (3+x)/(x+19)=3/5 | | x3x+8=44 | | 4b–=(9b–8) | | 9u+1=-26u= | | 3x=66x+5 | | 8k×5=20÷5 | | 64=-4(-1+5x) | | 24.5=3.5x | | p−373=496 | | 3r-6-4r=8 | | 24=k•4 | | g/26=7 | | g/26= | | 60=11x+38 | | -3.39-5.5m=9.35+8.4m+6.72 |